Blasenaugmentation und -ersatz bei Kindern und Jugendlichen = Bladder augmentation and urinary diversion in children and adolescents - Stein, Raimund; Wessel, Lucas; Michel, Maurice Stephan (Der Urologe, 2016)
Background: In children and adolescents, the indication for continent urinary diversion or bladder augmentation is rare. Today, for most patients with a neurogenic bladder, conservative treatment (clean intermittent catheterization [CIC] and pharmacotherapy) is the method of choice, while for patients with bladder exstrophy-epispadias complex (BEEC), primary reconstruction is recommended. Only after failure of conservative treatment or primary reconstruction should bladder augmentation or urinary diversion be considered. Other rare indications include patients with malignant tumor involving the lower urinary tract (e. g., rhabdomyosarcoma). Discussion: In patients with a hyperreflexive, small capacity, and/or low compliance bladder with a normal upper urinary tract, bladder augmentation (bowel segments/ureter) is an option. For those unable to perform CIC via the urethra, a continent cutaneous stoma should be offered. In patients with irreparable sphincter defects and normal renal function, a continent cutaneous diversion is an option and in those with a competent anal sphincter the rectosigmoid pouch can be offered. Conclusion: In this review, surgical options with their advantages and disadvantages are discussed.
Gesehen am 22.01.2019
Online publiziert:11. Dezember 2015